THE EFFECT OF ONLINE GAMES ON ENGLISH STUDENTS' VOCABULARY MASTERY - Windra Faresyah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Online games are one of the keys for learning and acquiring vocabulary by creating an interactive and motivating context to acquire new words. Online games potentially benefits in vocabulary acquisition as people can meet the person from another country to practice their knowledge about the vocabulary. Thus, the researcher is interested in studying the effect of playing online games on students’ English vocabulary mastery. This study used ex post facto research design involving 42 students from the 5th semester of the English department from the University of Islam Malang. The data are analyzed independent sample t test to measure the difference of vocabulary mastery of frequent and moderate gamers. In result shows that there is significant correlation between students’ habit in playing online game and students’ vocabulary mastery. This indicates that the better students’ habit in playing online games using English setting the better their vocabulary mastery. However, the result indicates that there is no significant difference between frequent and moderate gamers because the mean score of frequent gamers have slight difference with those of moderate gamers.Key Words: Online gaming, vocabulary mastery, comparison